Care in Early Learning and Childcare Transitions - McKenzie, Megan (International Journal of Educational and Life Transitions, 2023)
There has been a global trend in the expansion of Early Learning and Childcare (ELC) provision meaning more children of younger ages accessing ELC and experiencing the associated transitions than was previously the case. This has occurred within an increasingly Neoliberal context, with a greater focus on measurable educational outcomes, which are often placed as juxta positioned to care, which may prove challenging to define and quantify. These challenges are compounded when considering the often taken for granted nature of care in ELC, rendering it often unspoken and therefore at greater risk of being undermined or deemed a dispensable aspect of the increasingly multifaceted role. Given the above context, it was deemed essential that the concept of care was explicitly and critically explored in relation to the many multiple and multidimensional transitions which occur in ELC. This paper considers the criticality of care as part of ELC transitions by reviewing literature from 2010-present day. Findings suggested the role of ELC has shifted over time, leading to ambiguities and sometimes tensions in expectations between and within stakeholders. This in turn has influenced how care is defined, enacted and valued within ELC, with the overwhelming literature suggesting care is viewed less highly than education, for reasons such as difficulties in quantifying quality of care and the perception that care is innate rather than skilful. Transition practices were considered in relation to previously discussed definitions of care, which led to the identification of how care is enacted during ELC transitions.
Keywords: Early learning and childcare; care; transition